2021
DOI: 10.1186/s12913-020-06023-6
|View full text |Cite
|
Sign up to set email alerts
|

To do or not to do – a survey study on factors associated with participating in the Danish screening program for colorectal cancer

Abstract: Background Screening programs for colorectal cancer (CRC) exist in many countries, and with varying participation rates. The present study aimed at identifying socio-demographic factors for accepting a cost-free screening offer for CRC in Denmark, and to study if more people would accept the screening offer if the present fecal test was replaced by a blood test. Methods We used a cross-sectional survey design based on a representative group of 6807… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Further, there could be doubts about the extent to which hypothetical questions about future behavior are valid predictions of actual future behavior. However, in another study, we found no difference in predictors for participation in the national Danish colon cancer screening program by those who already had participated and those who were not yet eligible due to being too young and who instead reported their anticipated willingness to take part [71]. Yet, screening and treatment decisions might not be entirely comparable.…”
Section: Strengths and Limitationscontrasting
confidence: 65%
“…Further, there could be doubts about the extent to which hypothetical questions about future behavior are valid predictions of actual future behavior. However, in another study, we found no difference in predictors for participation in the national Danish colon cancer screening program by those who already had participated and those who were not yet eligible due to being too young and who instead reported their anticipated willingness to take part [71]. Yet, screening and treatment decisions might not be entirely comparable.…”
Section: Strengths and Limitationscontrasting
confidence: 65%
“…Research shows that obesity affects the likelihood of CRC screening discontinuation [ 38 ]. A Dutch survey also found that obesity was related to an obvious reduction in screening for CRC (OR: 0.8, 0.66–0.97) [ 39 , 40 ]. This is unclear for why obese people have a lower adherence to CRC screening recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Several international qualitative studies [132][133][134][135][136][137][138] have concluded that there are numerous psycho-social and cultural factors that interact and accumulate to impact on a patient's willingness to participate in CRC screening. Barriers include low awareness and a misunderstanding of the medical guidelines around the need for CRC screening and/or believing that screening was only required in the presence of symptoms, which is exacerbated by a lower perception of risk associated with bowel cancer compared with other more high-profile cancers [139].…”
Section: Interaction Between Patient and Healthcare Systemmentioning
confidence: 99%